Depression among medical students in Goa - Shreya Rai; Amit Dias (Wolters Kluwer Medknow Publications, 2015)
Background: Depression is the most common pervasive disorder and leading cause of disability and suicide worldwide. Medical curriculum could be demanding and stressful. There is limited data on stress and depression among medical students. This study was designed to find out the current status of depression among medical students and understand associated factors to help in taking early preventive and corrective measures. Methodology: This study was conducted over a period of 6 months among medical students at Goa Medical College who were selected using stratified random sampling. Data was collected using a structured performa and the General Health Questionnaire (GHQ12) which measures depression and anxiety. Open ended questions were also asked. The data was analyzed using appropriate statistical tests. Results: A total of 193 students participated in the study of whom 36% (71) were males and 64% (122) females. Thirty two students (16.5%) were found to be depressed. The mean GHQ total score was found to be 2.2 (95% CI, 1.8, 2.5). Females and interns were found to have higher GHQ scores. The students most commonly complained of being constantly under strain (37 %), inability to concentrate (30%) and lack of sleep (28%). Conclusion: Depression was quite common among medical students particularly females and interns which is comparable to western literature. There is a need for early detection and management in order to prevent co morbidities and reduce the risk of suicide.